PERENCANAAN LANSKAP KAWASAN WISATA DANAU BANDAR KHAYANGAN DI RUMBAI PESISIR, PEKANBARU RIAU - Gusti Dianda Sari; Afra DN Makalew; Nizar Nasrullah (http://arl.faperta.ipb.ac.id/, 2018)
Pekanbaru Government is currently increasing development to provide the activities of population needs. One of the development activities undertaken is development in the tourism sector. Bandar Khayangan Lake located in the district of Rumbai Pesisir, Pekanbaru City. The area has the potential of natural resources that can be used as a tourist attraction. Development of the area can cause damage the environment so that is necessary to provide a plan that can maintain the sustainability of this area. This research aims to analyzing and optimize the potential of Bandar Khayangan Lake and make a plan to create sustainable tourism areas. The result of research shows that most of the area is suitable to be used as tourist destination. Based on the analysis to keep the area sustainable, Bandar Khayangan Lake is divided into three zones between intensive zones, semi-intensive zones and non-intensive zones. The landscape plan consist of space plan, circulation, activities and facilities, and vegetation.